A clustering approach to identify the organizational life cycle - Atefeh Mousavi; Mehdi Mohammadzadeh; Hossein Zare (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This is an analytical, descriptive, and cross-sectional case study to identify a pharmaceutical company's organizational life cycle (OLC) situation using clustering methods. Data came from Iran's pharmaceutical firms in 2001-2018. We used sales growth, dividend per ratio, and performance indicators, including the return on assets, return on equity, Qtubin, and net profit of 342 firm-years to identify the OLC situation of pharmaceutical companies. We used principal component analysis and cluster analysis to define the company's OLC situation. Results show that 41.39% of the firm-years was in the growth stage, 34.14% in the maturity stage, and 17.22% in the decline stage. There was no significant difference between the average age in the three pharmaceutical companies' clusters. Study findings may guide policymakers towards more evidence-informed planning, and generic producers by providing more insights about their situation from an organizational life cycle perspective, giving them proper strategies to overcome accompanying challenges in pharmaceutical firms in Iran and countries with similar situations.
Keywords: 650; clustering methods; open innovation; organizational life cycle; pharmaceuticals